2023
DOI: 10.1038/s41467-023-35994-3
|View full text |Cite|
|
Sign up to set email alerts
|

CPEB1-dependent disruption of the mRNA translation program in oocytes during maternal aging

Abstract: The molecular causes of deteriorating oocyte quality during aging are poorly defined. Since oocyte developmental competence relies on post-transcriptional regulations, we tested whether defective mRNA translation contributes to this decline in quality. Disruption in ribosome loading on maternal transcripts is present in old oocytes. Using a candidate approach, we detect altered translation of 3’-UTR-reporters and altered poly(A) length of the endogenous mRNAs. mRNA polyadenylation depends on the cytoplasmic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Third, RIP assay showed that CPEB1 directly binds to the mRNA of p62 (Figure 3 I). Finally, because CPEB1 regulates protein translation by promoting or inhibiting poly(A) elongation 8 , we performed a poly(A) tail length assay followed by Sanger sequencing, which showed that CPEB1 attenuated poly(A) tail elongation at the 3'-UTR of p62 mRNA (Figure 3 J). Taken together, these data suggest that CPEB1 loss promotes p62 translation by facilitating poly(A) elongation of its mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Third, RIP assay showed that CPEB1 directly binds to the mRNA of p62 (Figure 3 I). Finally, because CPEB1 regulates protein translation by promoting or inhibiting poly(A) elongation 8 , we performed a poly(A) tail length assay followed by Sanger sequencing, which showed that CPEB1 attenuated poly(A) tail elongation at the 3'-UTR of p62 mRNA (Figure 3 J). Taken together, these data suggest that CPEB1 loss promotes p62 translation by facilitating poly(A) elongation of its mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Even though this is the opposite of what is seen in the Fmr1 KO mouse brain cortex, and in FMRP KO cell lines, it is possible that this is true in this specific context. These oocytes are of poor quality and resemble those from a much older wildtype female, and studies have demonstrated a decline in both CPEB1 and FMRP levels in aged females, although a causal link has not been established (Takahashi et al, 2015;Takahashi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…At a molecular level, we sought to connect the observed phenotypes to the cytoplasmic polyadenylation machinery and its regulation via FMRP. The CPEB1 protein is known to be critical for oogenesis and oocyte maturation in flies, zebrafish and mice (Bally-Cuif et al, 1998; Christerson and Mckearin, 1994; Hake and Richter, 1994; O’Connell et al, 2014; Takahashi et al, 2023). A functional interaction between FMRP and CPEB1 is also well reported in multiple contexts, where both proteins regulate each other’s activities, predominantly in an antagonistic fashion (Oe et al, 2022; Shin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned briefly in the Introduction, maternal age affects female reproductive organs in mammals. Oocyte quality is determined by processes including oocyte maturation, division spindle formation, energy supply, syngamy, early embryonic development, and epigenetics [2,[21][22][23]. The number of oocytes is a crucial issue that decreases with age [24].…”
Section: Effect Of Maternal Age On Oocytesmentioning
confidence: 99%